A Review of The Factors That Form The Brand Equity of Public Hospitals: A Quantitative Study in Tangerang City - Syah, Tantri Yanuar Rahmat; Ariyanti, Oktaria Dwi; Suyitno, Edi; Rojuaniah , Rojuaniah; Astuti, Puji (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study adopts a quantitative approach to investigate the factors that influence the brand equity of general hospitals in Tangerang. Using online questionnaires and structured survey methods, data was collected from 180 respondents who met the set criteria, with the majority of them being female. Variables such as brand awareness, brand loyalty, brand reputation, brand image, and brand equity were measured using a Likert scale with adequate validity and reliability analysis. A company's brand can reflect the value of the products it offers, but the brand will not be meaningful without strong equity in the market. Today, the ability to build brand equity plays an important role in creating value for customers and companies. Brand equity adds value to a product. Results from the structural equation model (SEM) analysis show that brand awareness and brand loyalty significantly contribute to RSU brand equity. However, the findings also show that brand image and brand reputation, although important, do not have a significant impact on brand equity. Limitations of the study include the specific sample representation and measurement methods used, which may affect the generalizability of the results. Therefore, future studies are recommended to take a broader comparative approach and deepen understanding with a qualitative approach to consumer perceptions of healthcare services